A review of the performance metrics and entrepreneurial practices of economics and business departments in UK universities: a ‘Gresham’s Law’ threat? - Alexiou, Constantinos; Saridakis, George (Sage, 2025)
Entrepreneurial approaches and privatisation practices have been widely embraced by academic and professional leadership teams in UK universities, arguably to ensure that the existing chasm between universities and society is bridged. Departments specialising in economics and business have transformed into mechanisms for disseminating knowledge reconfigured to meet the social and economic demands of the contemporary ‘entrepreneurial’ university. This article, through a comprehensive review of the extant literature, argues that the entrepreneurial practices and performance-driven metrics adopted by UK universities have largely suppressed academic pluralism, theoretical development and heterodox thinking. We are of the view that market practices, in conjunction with managerial-type approaches aimed at satisfying specific institutional and individual performance metrics, raise ethical concerns that undermine the established role of academia. The preservation of the university’s traditional role as an institution that promotes intellectual inquiry and pluralism, seeking factual and new knowledge by cultivating virtues and creativity, requires renunciation of the current model, which has transformed universities into ‘businesses’, and academics into ‘entrepreneurs’. Several alternative propositions are offered which, if considered, may help restore the sacrosanct role of the university as an institution of paideia.